Establishing and evaluating physician-pharmacist collaborative clinics to manage patients with type 2 diabetes in primary hospitals in Hunan province: study protocol of a multi-site randomized controlled trial in the era of COVID-19 pandemic - Sheng-Lan Tan; Jie Xiao; Hai-Yan Yuan; Lei Chen; Qing Wang; Da-Xiong Xiang; Xia Li; Yan-Gang Zhou; Yan Guo; Hai-Ying Huang; Dan-Hui Zhao; Yue Li; et al. (BMC, 2022)
Abstract Background The COVID-19 pandemic has exerted an unprecedented and universal impact on global health system, resulting in noticeable challenges in traditional chronic disease care, of which diabetes was reported to be most influenced by the reduction in healthcare resources in the pandemic. China has the world's largest diabetes population, and current diabetes management in China is unsatisfactory, particularly in rural areas. Studies in developed countries have demonstrated that physician-pharmacist collaborative clinics are efficient and cost-effective for diabetes management, but little is known if this mode could be adapted in primary hospitals in China. The aim of this proposed study is to develop and evaluate physician-pharmacist collaborative clinics to manage type 2 diabetes mellitus (T2DM) in primary hospitals in Hunan province. Methods A multi-site randomized controlled trial will be conducted to evaluate the effectiveness and cost-effectiveness of the physician-pharmacist collaborative clinics compared with usual care for Chinese patients with T2DM. Six primary hospitals will participate in the study, which will recruit 600 eligible patients. Patients in the intervention group will receive services from both physicians and pharmacists in the collaborative clinics, while the control group will receive usual care from physicians. Patients will be followed up at the 3rd, 6th, 9th and 12th month. Comparison between the two groups will be conducted by assessing the clinical parameters, process indicators and costs on diabetes. A satisfaction survey will also be carried out at the end of the study. Discussion If effective, the physician-pharmacist collaborative clinics can be adapted and used in primary hospitals of China to improve glycemic control, enhance medication adherence, decrease incidence of complications and reduce patients' dependence on physicians. Findings from the present study are meaningful for developing evidence-based diabetes care policy in rural China, especially in the COVID-19 pandemic era. Trial registration Chinese Clinical Trial Registry, ChiCTR2000031839 , Registered 12 April 2020.